Inheritance Rights Of Unmarried Children In Indonesian Civil Law: A Normative And Comparative Study - Mayangsari, Nur; Watofa, Yohana; Sassan, Jonhi (Mawaddah: Jurnal Hukum Keluarga Islam, 2024)
Amidst the increasing trend of pre-marital relationships and infidelity in Indonesia, The number of children born outside of marriage has also risen. However, ironically, these children are often marginalized by social stigma and discrimination, and experience uncertainty about their legal rights, including inheritance rights. This study examines the normative and comparative aspects of the inheritance rights of children born out of wedlock in Indonesian civil law. Rights of inheritance of children born out of wedlock are restricted to the estates of their mother and the mother's family, according to Indonesian legal tradition, as laid out in the Civil Code (KUHPerdata). But with the Constitutional Court's ruling No. 46/PUU-XIV/2017, which expanded their right to inherit from their biological father under some circumstances, a breath of fresh air arrived. Using a qualitative normative and comparative approach, this study examines the Constitutional Court's ruling, the Civil Code, and the Collection of Islamic Law (KHI).  A comparison of the inheritance rights of out-of-wedlock children in Indonesia with other countries is also conducted. The research findings show that although extramarital children were initially excluded from their father's inheritance, they are now recognized as having such rights under certain conditions. However, the implementation of this decision is still hindered by social stigma and lack of public awareness. To ensure efficient execution and handle ongoing socioeconomic difficulties, Indonesia's inheritance rights for children born out of wedlock are a complex and dynamic matter that requires ongoing work.